Drugs in anaesthesia and intensive care. - Smith, S. P. (Susan P.); Scarth, Edward ([Oxford] : Oxford University Press, 2016)
Anesthetists can make use of a wide range of drug treatments and this book provides readily available and accessible information on the appropriate drug to use in any given situation.
Includes index.
Description based on online resource; title from home page (viewed on February 17, 2016).
Keywords: Anesthetics; Critical care medicine